Three-step method ITO-Ag-ITO etching solution, and preparation method and application thereof
By using components such as acetic acid, citric acid, ascorbic acid and hydrofluoric acid in the ITO-Ag-ITO etching solution, combining the reducing properties of aldehyde compounds, the problem of too fast etching rate of the Ag layer is solved, and stable etching is achieved Rate and morphology modification, suitable for OLED pixel electrode manufacturing.
Patent Information
- Application Number
- CN202411154050.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-17
AI Technical Summary
The etching rate of the Ag layer in the existing three-step ITO-Ag-ITO etching solution is too fast, resulting in excessive CD-loss of the Ag layer and lack of protection for the Ag layer, which affects the morphological quality of the OLED pixel electrode manufacturing process.
Using a three-step ITO-Ag-ITO etching solution containing acetic acid, citric acid, ascorbic acid and hydrofluoric acid, the side corrosion amount is reduced by reducing the aldol compounds and compatible with the etching of the TiAlTi layer under an acidic environment. Stable etching rate and morphological modification.
The CD-loss of the Ag layer is significantly reduced, process efficiency is improved, stable etching rate for Ag and ITO is ensured, and better morphological control and industrial application potential is provided in OLED manufacturing.
Smart Images

Figure CN119144333A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to etching liquid technology, in particular to a three-step ITO-Ag-ITO etching liquid, a preparation method and application thereof. Background Art
[0002] ITO-Ag-ITO etching liquid is mostly used for etching pixel electrodes in the manufacturing process of liquid crystal displays (TFT-LCD) and organic light-emitting diodes (OLED). Currently, the commercial ITO-Ag-ITO etching methods can be divided into the following three types according to their process steps:
[0003] One-step method: Use ITO-Ag-ITO etching solution to etch ITO and Ag stacks in one process step. The advantage is that the process is simple and the equipment requirements are low; the disadvantage is that the same etching solution is used to etch two material stacks with huge differences in corrosion rates, which can easily lead to morphological defects.
[0004] Two-step method: In the first step, ITO-Ag etching solution is used to etch top-ITO and Ag, and in the second step, a special ITO etching solution is used to etch bottom-ITO and modify the morphology of the top-ITO+Ag layer. The process and equipment requirements are more complicated than the one-step method, but step-by-step etching makes the process easier to adjust and can also obtain better morphology. There is also a reverse process in the industry, that is, in the first step, a special ITO etching solution is used to etch top-ITO, and in the second step, an ITO-Ag etching solution is used to etch bottom-ITO and Ag.
[0005] Three-step method: The etching process is divided into three steps. The upper and lower ITO layers are etched with ITO etching solution, and the middle layer of Ag (the very small amount of ITO remaining) is etched with Ag etching solution. The three-layer etching process can adjust the process parameters in each step separately, and can achieve more precise morphology control.
[0006] In the common three-step ITO-Ag-ITO etching process, the first and third steps use oxalic acid or mixed acid solution to etch ITO, and the second step uses ITO-Ag-ITO etching solution to etch Ag (which may also corrode part of the top / bottom ITO). Due to the lack of ITO to protect the Ag layer, the second step will etch the Ag layer faster even at 25°C. In normal processes, the amount of side etching of the Ag layer can only be controlled by controlling the process time. Summary of the invention
[0007] The purpose of the present invention is to propose a three-step ITO-Ag-ITO etching solution for the problem that the above-mentioned traditional three-step ITO-Ag-ITO etching solution has a too fast etching rate for the Ag layer and the CD-loss of the Ag layer is too large. The etching solution has a stable etching rate for ITO-Ag-ITO, does not damage the insulating layer and the photoresist, can be used in the manufacturing process of OLED pixel electrodes, and is used to solve the problem that the CD-loss of the Ag layer is too large during the three-step ITO-Ag-ITO etching process; and hydrofluoric acid is introduced into the system, which is compatible with the etching and morphology modification of the TiAlTi layer in the through-hole process.
[0008] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.
[0009] To achieve the above object, the technical solution adopted by the present invention is: a three-step ITO-Ag-ITO etching solution, comprising the following components in weight proportions:
[0010]
[0011] Furthermore, the organic acid is one or more of acetic acid, citric acid, tartaric acid, oxalic acid, glycolic acid, ascorbic acid, trichloroacetic acid and trinitrobenzenesulfonic acid.
[0012] Furthermore, the organic acid is preferably acetic acid, citric acid and ascorbic acid.
[0013] Furthermore, the mass ratio of the acetic acid, citric acid and ascorbic acid is 8-5:8-3:3-1.
[0014] Furthermore, the mass ratio of the acetic acid, citric acid and ascorbic acid is preferably 5:4:1.
[0015] Furthermore, the organic acid is 8-10 parts.
[0016] Among the organic acids, acetic acid and citric acid are low-priced and environmentally friendly. In addition to providing acidity, the carboxyl groups can chelate metal ions, and ascorbic acid can provide reducing properties.
[0017] Furthermore, the inorganic acid is one or more of nitric acid, hydrofluoric acid, sulfuric acid, hydrochloric acid and phosphoric acid.
[0018] Furthermore, the inorganic acid is preferably nitric acid and hydrofluoric acid.
[0019] Furthermore, the mass ratio of the nitric acid to the hydrofluoric acid is 7 to 10:1.
[0020] Furthermore, the mass ratio of the nitric acid to the hydrofluoric acid is preferably 7:1.
[0021] Furthermore, the inorganic acid is 2-4 parts.
[0022] The inorganic acid of the present invention can provide oxidizing properties for etching metals, such as nitric acid providing the necessary oxidizing properties for etching Ag, ITO, Ti, and Al, and hydrofluoric acid can etch metal Ti. When the inorganic acid includes hydrofluoric acid, compatible etching of the peripheral through-holes and the TiAlTi layer at the circuit position can be achieved in an acidic environment, thereby improving process efficiency.
[0023] Furthermore, the aldehyde compound is one or more of octanal, butyraldehyde, benzaldehyde and valeraldehyde.
[0024] Furthermore, the aldehyde compound is preferably octanal.
[0025] Furthermore, the aldehyde compound is 1-2 parts.
[0026] The aldehyde compound of the invention can reduce metal ions and reduce the amount of side corrosion.
[0027] Furthermore, the sulfur-containing organic acid sodium salt is one or more of sodium thioglycolate, sodium methanesulfonate, sodium p-toluenesulfonate and sodium mercaptopropionate.
[0028] Furthermore, the sulfur-containing organic acid sodium salt is preferably sodium thioglycolate.
[0029] Furthermore, the amount of the sulfur-containing organic acid sodium salt is 2-4 parts.
[0030] Furthermore, the ultrapure water is 35-45 parts.
[0031] The three-step ITO-Ag-ITO etching solution of the present invention is transparent or light yellow.
[0032] Another object of the present invention is to disclose a method for preparing the three-step ITO-Ag-ITO etching solution, comprising the following steps: weighing each component separately, adding all the components into a container, and stirring until all the materials are completely dissolved to prepare the three-step ITO-Ag-ITO etching solution.
[0033] Another object of the present invention is to disclose the application of the three-step ITO-Ag-ITO etching solution in the field of etching ITO-Ag-ITO composite layers and / or the field of etching and morphology modification of TiAlTi layers in through-hole processes.
[0034] Furthermore, the three-step ITO-Ag-ITO etching solution is used to etch the ITO-Ag-ITO intermediate layer Ag.
[0035] Further, the method of etching the ITO-Ag-ITO composite layer using a three-step ITO-Ag-ITO etching solution comprises the following steps:
[0036] Step 1: Immerse the substrate coated with the ITO-Ag-ITO composite layer in the oxalic acid ITO etching solution to perform the first step of etching to complete the top-ITO etching; the etching time is 40-80s, and the etching temperature is 40-50°C;
[0037] Step 2: immersing the substrate after the first step of etching in the three-step ITO-Ag-ITO etching solution, performing the second step of etching, completing the etching of the intermediate layer Ag (and simultaneously etching the ITO that was not completely removed in step 1); the etching time is 50-150s, and the etching temperature is 20-30°C;
[0038] Step 3: Immerse the substrate after the second step of etching in oxalic acid ITO etching solution, perform the third step of etching, and complete the bottom-ITO etching; the etching time is 40-80s, and the etching temperature is 40-50°C.
[0039] Furthermore, the oxalic acid concentration in step 1 is 3.4 wt%.
[0040] Furthermore, the etching time in step 1 is 50-70s.
[0041] Furthermore, the etching temperature in step 1 is 45°C.
[0042] Furthermore, the etching time in step 2 is 80-110s.
[0043] Furthermore, the etching temperature in step 2 is 25°C.
[0044] Furthermore, the oxalic acid concentration in step 1 is 3.4 wt%.
[0045] Furthermore, the etching time in step 3 is 50-70s.
[0046] Furthermore, the etching temperature in step 3 is 45°C.
[0047] Unless otherwise specified, % in the present invention refers to mass percentage.
[0048] The three-step ITO-Ag-ITO etching solution, preparation method and application thereof of the present invention have the following advantages compared with the prior art:
[0049] 1) The present invention uses aldehyde compounds and organic acids. Aldehydes have reducing properties, thereby reducing metal ions and reducing the amount of side etching. Organic acids also have strong reducing properties and can also exist as stabilizers for aldehyde compounds. In particular, when the organic acid includes ascorbic acid and the aldehyde includes octanal, ascorbic acid, as a stabilizer, can stabilize octanal through its antioxidant properties; on the other hand, when ascorbic acid is oxidized to dehydroascorbic acid and octanal is oxidized to the corresponding carboxylic acid, Ag+ can be reduced to metallic Ag, significantly reducing the CD-loss after the Ag layer is etched.
[0050] 2) When the inorganic acid in the etching solution of the present invention includes hydrofluoric acid, compatible etching of the TiAlTi layer at the peripheral through hole and the circuit position can be achieved in an acidic environment, thereby improving process efficiency.
[0051] 3) The etching solution of the present invention has no strong volatile components, has good stability over time, and has a stable etching rate for Ag and ITO.
[0052] Therefore, the three-step ITO-Ag-ITO etching solution of the present invention has very good application prospects and large-scale industrial promotion potential in the field of display panels, especially in the field of OLED pixel electrode manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a SEM image of ITO-Ag-ITO after being treated with etching solution in Comparative Example 2, magnified 35,000 times;
[0054] Figure 2 This is a SEM image of ITO-Ag-ITO after being treated with etching solution in Comparative Example 2, magnified 35,000 times;
[0055] Figure 3 This is a SEM image of ITO-Ag-ITO after being treated with the etching solution in Example 1, magnified 35,000 times;
[0056] Figure 4 This is a SEM image of ITO-Ag-ITO after being treated with the etching solution in Example 1, magnified 35,000 times;
[0057] Figure 5 This is a SEM picture of the TiAlTi wire layer after being treated with etching solution in Comparative Example 2, magnified 40,000 times;
[0058] Figure 6 This is a SEM picture of the TiAlTi wire layer after being treated with the etching solution in Example 1, magnified 40,000 times. DETAILED DESCRIPTION
[0059] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:
[0060] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0061] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0062] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.
[0063] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0064] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.
[0065] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.
[0066] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0067] Examples 1-9
[0068] Examples 1-9 disclose a variety of three-step ITO-Ag-ITO etching solutions, the components and weight ratios of which are shown in Table 1. The preparation method is as follows: weigh each component separately, add all the components into a container, and stir until all the materials are completely dissolved to prepare a three-step ITO-Ag-ITO etching solution.
[0069] Table 1 Components and weight ratios of the three-step ITO-Ag-ITO etching solution of Examples 1-9
[0070]
[0071] Comparative Example 1-2
[0072] Comparative Example 1-2 discloses two etching solutions, the components and weight ratios of which are shown in Table 2, and the preparation methods thereof are the same as those of Example 1.
[0073] Table 2 Components and weight ratios of etching solutions in comparative example 1-2
[0074]
[0075] The various properties of the above embodiments or comparative examples are tested below.
[0076] Table 3 Test data
[0077]
[0078] As shown in Table 3, the three-step ITO-Ag-ITO etching solution of Examples 1-9 can significantly reduce the double-sided CD-loss of the Ag layer through the synergistic effect of aldehyde compounds and ascorbic acid. Except for Example 9 which does not contain ascorbic acid and has a top Ti protrusion, the TiAlTi layer after etching has a step morphology. Comparative Examples 1-2 do not contain aldehyde compounds, and cannot effectively reduce Ag ions, resulting in a high double-sided CD-loss of the Ag layer; and Comparative Example 2 does not contain a F ion source, and cannot etch the Ti layer, so a protruding morphology of the Ti layer appears.
[0079] Figure 1 This is a SEM image of ITO-Ag-ITO after being treated with etching solution in Comparative Example 2, magnified 35,000 times; Figure 2 This is a SEM image of ITO-Ag-ITO after being treated with etching solution in Comparative Example 2, magnified 35,000 times; Figure 3 This is a SEM image of ITO-Ag-ITO after being treated with the etching solution in Example 1, magnified 35,000 times; Figure 4 This is a SEM image of ITO-Ag-ITO after being treated with the etching solution in Example 1, magnified 35,000 times; Figure 5 This is a SEM picture of the TiAlTi wire layer after being treated with etching solution in Comparative Example 2, magnified 40,000 times; Figure 6 This is a 40,000-fold magnified SEM image of the TiAlTi conductor layer after etching solution treatment in Example 1. As can be seen from the figure, the bilateral CD-loss of the Ag layer after the three-step ITO-Ag-ITO etching solution treatment in Example 1 is significantly lower; for the morphology modification of the TiAlTi layer, after etching solution treatment in Example 1, the morphology is stepped, and there is no obvious top Ti protrusion; while the top Ti protrusion appears in Comparative Example 2, and the obvious top Ti protrusion will cause obvious pores after the back-end process material is covered, affecting the yield.
[0080] in:
[0081] The test method for performance 1CD-loss is:
[0082] The ITO-Ag-ITO samples were etched using the etching solutions of the above embodiments and comparative examples of the present invention, and then cleaned after etching. The specific steps are as follows:
[0083] Step 1: Immerse the substrate coated with the ITO-Ag-ITO composite layer in a 3.4wt% oxalic acid ITO etching solution to perform the first step of etching; the etching time is 60s and the etching temperature is 45°C.
[0084] Step 2: Immerse the substrate after the first step of etching in the etching solution of the embodiment or comparative example to perform the second step of etching; the etching time is 90 seconds and the etching temperature is 25°C.
[0085] Step 3: Immerse the substrate after the second step of etching in 3.4wt% oxalic acid ITO etching solution and perform the third step of etching; the etching time is 60s and the etching temperature is 45°C.
[0086] Step 4: Rinse the ITO-Ag-ITO substrate in ultrapure water for at least two times, and blow dry with nitrogen gas.
[0087] Step 5: Observe the sample morphology under SEM after FIB ion beam cutting and measure CD-loss.
[0088] The ultrapure water used in the above steps is deionized water with a resistance of at least 18 MΩ.
[0089] The test method for performance 2 etching rate is:
[0090] The pure Ti sample was etched using the etching solution of the embodiment and the comparative example, and then cleaned after etching. The specific steps are as follows:
[0091] Step 1: Heat the etching solution in a water bath to 25° C., immerse the sample in the etching solution and shake it at a gradient of 10 seconds until the metal on the surface of the sample is completely etched;
[0092] Step 2: Rinse the sample in ultrapure water at least twice and blow dry with nitrogen.
[0093] Step 3: Measure the thickness of the sample under SEM and calculate the average etching rate.
[0094] The test method for the morphology of performance 3TiAlTi after etching is:
[0095] The TiAlTi sample was etched using the etching solution of the embodiment and the comparative example, and then cleaned after etching. The specific steps are as follows:
[0096] Step 1: Immerse the TiAlTi substrate in an etching solution for etching; the etching time is 90 seconds and the etching temperature is 25°C.
[0097] Step 2: Rinse the TiAlTi substrate in ultrapure water at least twice and blow dry with nitrogen.
[0098] Step 3: Observe the sample morphology under SEM.
[0099] The ultrapure water used in the above steps is deionized water with a resistance of at least 18 MΩ.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A three-step ITO-Ag-ITO etching solution, characterized in that: The composition includes the following components in weight ratio:
2. The three-step ITO-Ag-ITO etching solution according to claim 1, characterized in that: The organic acid is one or more of acetic acid, citric acid, tartaric acid, oxalic acid, glycolic acid, ascorbic acid, trichloroacetic acid and trinitrobenzenesulfonic acid.
3. The three-step ITO-Ag-ITO etching solution according to claim 1, characterized in that: The inorganic acid is one or more of nitric acid, hydrofluoric acid, sulfuric acid, hydrochloric acid and phosphoric acid.
4. The three-step ITO-Ag-ITO etching solution according to claim 1, characterized in that: The aldehyde compound is one or more of octanal, butyraldehyde, benzaldehyde and valeraldehyde.
5. The three-step ITO-Ag-ITO etching solution according to claim 1, characterized in that: The sulfur-containing organic acid sodium salt is one or more of sodium thioglycolate, sodium methanesulfonate, sodium p-toluenesulfonate and sodium mercaptopropionate.
6. A method for preparing a three-step ITO-Ag-ITO etching solution according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: weighing each component respectively, adding all the components into a container, and stirring until all the materials are completely dissolved, so as to prepare a three-step ITO-Ag-ITO etching solution.
7. An application of the three-step ITO-Ag-ITO etching solution described in any one of claims 1 to 5 in the field of etching ITO-Ag-ITO composite layers and / or the field of etching and morphology modification of TiAlTi layers in through-hole processes.
8. The use according to claim 7, characterized in that: The three-step ITO-Ag-ITO etching solution is used in etching the ITO-Ag-ITO intermediate layer Ag.
9. The use according to claim 7, characterized in that: The method for etching the ITO-Ag-ITO composite layer using the three-step ITO-Ag-ITO etching solution comprises the following steps: Step 1: Immerse the substrate coated with the ITO-Ag-ITO composite layer in the oxalic acid ITO etching solution to perform the first step of etching; the etching time is 40-80s, and the etching temperature is 40-50°C; Step 2: immersing the substrate after the first step of etching in the three-step ITO-Ag-ITO etching solution to perform the second step of etching; the etching time is 50-150s, and the etching temperature is 20-30°C; Step 3: Immerse the substrate after the second step of etching in oxalic acid ITO etching solution and perform the third step of etching; the etching time is 40-80s, and the etching temperature is 40-50°C.
